Human dimensions of lead in the environment from ammunition and fishing tackle - Ross-Winslow, Danielle, author; Teel, Tara, advisor; Leong, Kirsten, committee member; Davies, Timothy, committee member (Colorado State University. Libraries, 2013)
Significant attention has been directed in recent years toward examining and addressing the impacts of lead in the environment from ammunition and fishing tackle. Lead issues are relevant to those interested in protecting the health of humans, wildlife, and ecosystems, such as national and regional land management agencies, national and state agencies that manage fish and wildlife resources, national and state health and human services agencies, and non-profit conservation and environmental research organizations. The topic of lead in the environment from ammunition and fishing tackle is also highly controversial among stakeholders. Strong and conflicting public opinions about the use of lead ammunition and fishing tackle make decision-making particularly challenging for agencies. This thesis presents two manuscripts that explore how human dimensions research can inform this process by providing a more adequate representation of diverse viewpoints and enhancing the ability of various entities interested in this issue to identify likely sources of controversy related to potential management activities, communicate more effectively with the public, and develop more successful management solutions. The first paper synthesizes the relevant literature regarding the use of lead in recreational hunting and fishing with specific objectives to overview: 1) trends in lead use in the U.S. and emerging awareness of the hazards to human health and the natural environment; 2) impacts of lead from hunting and fishing and specific measures, including regulatory and non-regulatory action, that have been introduced by agencies and organizations in the U.S. to reduce these impacts; and 3) results of recent human dimensions investigations aimed at addressing this issue. The second paper documents a basic interpretive qualitative research study that was undertaken in the summer of 2012. The purpose of this study was to better understand the meaning people assign to issues involving the use of lead ammunition and fishing tackle. More specific objectives related to (a) how stakeholders make sense of actions that are being pursued, or could be taken, to manage human activities with a view to prevent, reduce, or mitigate negative impacts to the environment, wildlife, and/or humans; and (b) what are crucial aspects of human thought about lead issues and management actions that can contribute to an understanding of the controversy surrounding this topic. The findings were able to identify different attitudinal positions with regard to lead use; different preferences for management strategies; and that differences were associated with conflict. More importantly, the research explored elements that were key to how meaning was constructed by individuals that correlated to these different elements.